Auditory Sentence Processing in Bilinguals: The Role of Cognitive Control - Akhavan, Niloofar; Blumenfeld, Henrike K.; Love, Tracy (Frontiers in Psychology, 2020)
A number of research studies have shown that the unique need in bilinguals to manage both of their languages positively impacts their cognitive control processes. Yet, due to a dearth of studies at the sentence level, it is still unclear if this benefit extends to sentence processing. In monolinguals and bilinguals, cognitive control helps in reinterpretation of garden path sentences but it is still unknown how it supports the real-time resolution of interference during parsing, such as the type of interference seen in the processing of object relative (OR) sentences. In this study, we compared monolinguals and bilinguals during online spoken OR sentence processing and examined if both groups used cognitive control to resolve interference. In this eye-tracking visual world (ETL-vw) study, OR sentences were aurally presented to 19 monolingual and 21 English-Spanish bilingual adults while gaze patterns were captured throughout the time course of the sentence. Of particular interest was the post-verb position, where the listener connects the verb to its direct object. In OR constructions (e.g., “The man that the boy pushes__ has a red shirt.”), the verb (‘pushes’) links to its syntactically licensed direct object (‘the man’) at verb offset. During syntactic linking, the parser crosses over an intervening noun phrase (NP, ‘the boy’) and the two NP activations create interference. The nature of this paradigm allows us to measure interference and its resolution between the intervening NP and the displaced object in real-time. By relating sentence processing patterns with cognitive control measures, high- and no- conflict N-Back tasks, we investigated group differences in the use of cognitive control during sentence processing. Overall, bilinguals showed less interference than monolinguals from the intervening NP during the real time processing of OR sentences. This interference effect and its resolution was significantly predicted by cognitive control skills for bilingual, but not monolingual listeners. This enhanced effect in bilinguals extends previous findings of interference resolution to real time spoken sentence processing suggesting that bilinguals are more efficient than monolinguals at managing interference during complex sentence processing.